Homocoupling Defects in a Conjugated Polymer Limit Exciton Diffusion. (16th September 2019) - Streiter, Martin; Beer, Daniel; Meier, Fabian; Göhler, Clemens; Lienert, Caroline; Lombeck, Florian; Sommer, Michael; Deibel, Carsten
Abstract: Copolymers such as PCDTBT (poly( N ‐9′‐heptadecanyl‐2, 7‐carbazole‐ alt ‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole))) are commonly employed as donor material in bulk heterojunction solar cells. Recently, chemical defects such as homocouplings have been shown to form at the material synthesis stage, strongly reducing the short circuit current in organic photovoltaics. Here it is shown that both low molecular weight and homocoupling defects reduce the short circuit current of solar cells because of limited exciton diffusion. A model that unites and explains the influence of both chemical parameters with the distribution of conjugation lengths is proposed. The connection between limited exciton diffusion and short circuit current is revealed via kinetic Monte Carlo simulation of bulk heterojunctions. The findings are likely applicable for copolymers in general. Abstract : The copolymer PCDTBT usually includes homocoupling defects. These homocoupling defects limit the short circuit current in organic solar cells. It is shown that low molecular weight and homocoupling defects both reduce the short circuit current because of limited exciton diffusion. A model is introduced that explains the influence of both chemical parameters with the changed distribution of conjugation lengths.